Comparative transcriptome analysis of MDBK cells reveals that BoIFN-γ augmented host immune responses to bovine herpesvirus 1 infection - Jiang, Bo; Wang, Jing; Liu, Wenxiao; Cheng, Jing; Xu, Jian; Cao, Mengyao; Li, Yongqing (Frontiers in Microbiology, 2022)
Bovine herpesvirus 1 (BoHV-1) is an alphaherpesvirus that causes infectious bovine rhinotra-cheitis and infectious pustular vulvovaginitis in cattle. Ιnterferon-gamma (IFN-γ) is a pleiotropic cytokine with antiviral activity that modulates the innate and adaptive immune responses. In this study, we prepared high-purity bovine interferon gamma (BoIFN-γ) dimer protein using pro-karyotic expression system and affinity chromatography. We subsequently investigated the effect of BoIFN-γ on BoHV-1 infection in Madin-Darby bovine kidney (MDBK) cells. The results showed that BoIFN-γ pretreament not only decreased the production of BoHV-1, but also reduced the cytopathic effect of the virus. Differential gene expression profiles of BoHV-1 infected MDBK cells were then analysed through high-throughput RNA sequencing. The data showed that BoIFN-γ pretreatment reduced lipid metabolism disorder and DNA damage caused by BoHV-1 infection. Furthermore, BoIFN-γ treatment upregulated the transcription of interferon regulatory transcription factors (IRF1 and GBP5) and interferon-stimulated genes (ISGs) of MDBK cells. Additionally, BoIFN-γ promotes expression of cellular protein involved in complement activation and coagulation cascades response as well as antigen processing and presentation process, while BoHV-1 infection dramatically downregulates transcription of these immune components in-cluding C3, C1r, C1s, PLAT, ITGB2, PROCR, BoLA, CD74, B2M, PA28, BoLA-DRA and TAPBP . Collectively, our findings demonstrate that BoIFN-γ pretreatment can improve host resistance to BoHV-1 infection by regulating transcription or expression of host protein associated with cellular metabolism and innate immune response. This provides insights into the devel-opment of prophylactic agents for prevention and control of BoHV-1 infection.